1980
DOI: 10.1007/bf00286058
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome polymorphism in the Italian newt, Triturus italicus

Abstract: A chromosomal variation, changing shape and C-banding pattern of chromosome XII of Triturus italicus was detected among the offspring of two F1 hybrid families of T. italicus female x T. vulgaris meridionalis male. In both families a number of individuals appeared to have a metacentric instead of the expected subtelocentric chromosome XII of T. italicus.--Investigations in three well separated localities in the range of the species showed the polymorphism to have a wide distribution and to be part of a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…2C). Ragghianti et al (1980); only the standard ST karyomorph of pair 12 is shown. Salamandra .salamandra karyotype is according to Mancino et al (1969).…”
Section: Salarnandridaementioning
confidence: 99%
“…2C). Ragghianti et al (1980); only the standard ST karyomorph of pair 12 is shown. Salamandra .salamandra karyotype is according to Mancino et al (1969).…”
Section: Salarnandridaementioning
confidence: 99%
“…Geographic variation among populations of T. italicus was studied by means of chromosome 12 C-banding (Ragghianti et al, 1980;Bucci-Innocenti et ai, 1983b), allozyme electrophoresis (Ragghianti & Wake, 1986;Cataudo et al, 2000), and outer morphology (Scillitani, 1992, Ph.D. Thesis, University of Napoli; Scillitani, 1998;Scillitani et al, 1993). The cited studies reveal a previously unexpected interpopulational variation and emphasize the need to consider intraspecific variability in phylogenetic studies of Triturus, otherwise a considerable amount of information would be lost.…”
Section: Discussionmentioning
confidence: 99%
“…Cogalniceanu & Venczel (1992) thought that most speciation and subspeciation events in the Paleotriton subgenus were caused by geographic isolation due to glaciations. Ragghianti & Wake (1986) analyzed the geographic variation of T. italicus by allozyme electrophoresis and explained their results by fragmentation of demes due to isolation in insular areas caused by transgression cycles (rather than glaciations), affecting southern Italy in the Pleistocene. Sparreboom (1987 and1989, combined data);19, Giacoma & Balletto (1988: consensus); 20, Macgregor et al (1990: combined data …”
Section: Zoogeographical Datamentioning
confidence: 99%
“…Indeed one of the few reports on chromosome changes within Triturus species refers to the appearance of pericentric inversions within T. italicus (Ragghianti et al, 1980). The comparison of C-banding patterns, even within a subspecific complex, such as Triturus alpestris, reveals notable differences in position and number of heterochromatic bands within the chromosome complement.…”
Section: Discussionmentioning
confidence: 99%